2016
DOI: 10.1007/s10266-016-0232-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root canal treatment procedures with a novel rotary nickel titanium instrument (TRUShape) on stress in mandibular molars: a comparative finite element analysis

Abstract: The aim of this study was to investigate and compare, via finite element analysis (FEA), the effects of endodontic access and canal preparation on stress distribution under functional loading of a mandibular molar treated with novel (TRUShape) and conventional (Vortex) rotary root canal preparation instruments. Identical plastic mandibular molars with natural anatomy had all 4 canals shaped with either TRUShape or a conventional rotary, Vortex (#20 and #30, both by Dentsply Tulsa Dental). Finite element analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Furthermore, photopolymerized resin root models were used instead of real teeth to ensure standardization. Bonessio et al (31) mentioned the reliability of plastic tooth models used in their study; based on their pilot study, they reported the maximum spatial discrepancy as <1%. According to them, resulting stress errors were at least an order of magnitude less.…”
Section: Basic Research-technologymentioning
confidence: 97%
“…Furthermore, photopolymerized resin root models were used instead of real teeth to ensure standardization. Bonessio et al (31) mentioned the reliability of plastic tooth models used in their study; based on their pilot study, they reported the maximum spatial discrepancy as <1%. According to them, resulting stress errors were at least an order of magnitude less.…”
Section: Basic Research-technologymentioning
confidence: 97%
“…, Dejak & Mlotkowski , Bonessio et al . ). In case of oblique loading, the tooth experiences bending.…”
Section: Discussionmentioning
confidence: 97%
“…, Bonessio et al . ). According to the present results, the root filled teeth had higher P max stresses compared with the intact models in accordance with previous studies (Zelic et al .…”
Section: Discussionmentioning
confidence: 97%
“…Different simulated material properties (Young’s modulus (E) and Poisson’s ratio values) were generated, based on data from the literature (Table 2). 15,17,19 Cross-sections of root canal were created from the apex at intervals of 1.0 mm. To visualize the stress distributions and magnitudes in the models, the data were transformed into color graphics.…”
Section: Methodsmentioning
confidence: 99%